Chemical, Biological, Radiological, Nuclear, and Explosive (CBRNe) Preparedness: Perceptions of Australian Emergency Department (ED) Doctors and Nurses. Issue Volume 34:Issue s1(2019) (May 2019) - Hammad, Karen; Ranse, Jamie; Mortelmans, Luc
Abstract : Introduction: Clinicians working in emergency departments (ED) play a vital role in the healthcare response to chemical, biological, radiological, nuclear, and explosive (CBRNe) events. However, ED clinicians' individual and workplace preparedness for CBRNe events is largely unknown. Aim: The aim of this research was to explore Australian ED nurses and doctors' perceptions of individual and workplace preparedness related to CBRNe events. Methods: The study populations were Australian nurses and doctors who work in EDs. Data was collected via a survey with 43 questions requiring binary responses or a rating on a Likert scale. The survey consisted of questions relating to the participant's previous disaster training, perceived likelihood of a CBRNe event impacting their ED, perceived level of knowledge, perceived personal preparedness, perception of ED preparedness, and willingness to attend their workplace. Data were analyzed using descriptive and inferential statistics. Results: There were 244 complete responses, 92 (37.7%) doctors and 152 (62.3%) nurses. When comparing doctors and nurses, there was a statistical difference between gender (p = < 0.001), length of employment (p = < 0.001), and role in the ED (p = < 0.001). Doctors and nurses had a similar level of previous training except for practical training in mask fitting (p = 0.033). CBRNe events were considered separately. Perceived level of knowledge, perceived personal preparedness, and perception of ED preparedness were significant predictors of willingness to work in all CBRNe event. Perceived likelihood of a CBRNe event impacting their ED was not a predictor of willingness. Discussion: This research contributes to an overview of the current status of Australian ED clinicians' preparedness for CBRNe response. To increase the willingness of ED doctors and nurses attending their workplace for a CBRNe event, strategies should focus on enhancing individuals perceived level of knowledge, perceived personal preparedness, and perception of ED preparedness.